Perceived influences on post-diagnostic dietary change among a group of men with prostate cancer - Kassianos, Angelos P.; Coyle, Adran; Raats, Monique (My University, 2015)
A cancer diagnosis is often associated with loss of agency and control that can adversely affect well-being. Patients may try to regain control through dietary change aimed at preventing progression and/or recurrence. Evidence for the effectiveness of post-diagnostic dietary change in prostate cancer is not conclusive, which can cause uncertainty among patients and health professionals. This qualitative study explored how eight men in the U.K., who had been diagnosed with prostate cancer in the previous 5 years, accounted for any post-diagnostic changes they made to their diet. Data were generated through semi-structured telephone interviews and were subjected to thematic analysis. This yielded two themes concerning the perceived nature and importance of dietary change and the perceived determinants of dietary change. The latter focused on internal dimensions such as agency and external dimensions such as the perceived role of relationships with health professionals, the availability of credible dietary information and family influences. The study points to the importance of the family context in enabling the men to implement dietary change. It is suggested that, even if health professionals can only offer qualified, general advice about diet, this may provide men with a focus for action and a means of regaining control.
Keywords: Agency; Dietary change; Family; Gender; Prostate cancer; Thematic analysis